Construction failures of masonry and adobe buildings during the 2011 Van earthquakes in Turkey - Sayin, Erkut; Yon, Burak; Calayir, Yusuf; Gor, Mesut (Techno-Press, 2014)
On October 23, 2011, an earthquake of magnitude 7.0 struck Van, Turkey. This powerful earthquake caused the deaths of 604 people, more than 2,000 injuries, and a considerable loss of property. After this devastating earthquake, on November 9, 2011, another earthquake of magnitude 5.7 occurred. This moderate earthquake caused the deaths of 40 people. Partial and total collapse of the masonry and adobe buildings occurred in the rural areas of Van. In this paper, the acceleration records and response spectrums of the earthquakes were given and the structural deficiencies and reasons of the failures of the rural buildings were evaluated according to the Turkish Seismic Code. The observed failures showed that low quality of structural materials, poor workmanship, lack of engineering services and insufficient detailing of the structural elements are the main reasons of damages.
Keywords: masonry and adobe buildings; 2011 Van earthquakes; earthquake damage; structural deficiencies